ANALISIS KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN IPS DI SMP NEGERI 81 MALUKU TENGAH - Grace Maatoke; Franklin W. Ubra; Gerald Latuserimala (P3M Politeknik Negeri Ambon, 2022)
This research was conducted with the aim of knowing the pedagogic competence of social studies subject teachers at SMP Negeri 81 Central Maluku, This study uses a qualitative research type with a phenomology approach. The data collection techniques used are interviews, observation, and data analysis used, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that the pedagogic competence of social studies teachers at SMP Negeri 81 Maluku Tengah is said to be very good because it has been well fulfilled by social studies teachers including understanding students' characteristics from physical, social, moral, cultural, emotional, and intellectual aspects, understanding family background and student community and learning needs in a cultural context, understanding student learning styles and learning difficulties, facilitating the development of student potential, mastering theories and principles of learning and educational learning, developing curricula that encourage student involvement in learning, designing educational learning, implementing educational learning , assessing learning processes and outcomes. Keywords: Social Science Teacher Pedagogic Competence